Financial Capital and Production Demand for Value-Added Innovations in SMEs - Shaferi, Intan; Nawarini, Alisa Tri; Setyanto, Refius Pradipta (Journal of International Conference Proceedings, 2023)
SMEs have characteristics and an important role in the economy. Its independent characteristic makes it must be able to innovate. Innovation that has meaning with added value in innovation. Several influencing factors come from internal and external SMEs. Internal factors are believed to have a fundamental strength for SMEs to innovate. One of them that was used in this research was financial capital. In addition, external factors, also have meaning for innovation. In this research, production from demand was used as variable. This study aims to examine how financial capital and demand of production affect SME innovation. The research was conducted on one hundred SMEs in the Java region of Indonesia. The research was carried out post-pandemic, in first term of 2023. The research was conducted by analyzing the intervariable using the structural equation partial least square model. The research results that financial capital and demand for production influence innovation to create added value for SMEs. Through this research, it is hoped that SMEs will be able to find out that the financial capital factor needs to be strengthened to create innovation. Besides that, production demand also has a role in SMEs seeking innovation by providing added value to their production.